Female Sprague Dawley Rats Show Impaired Spatial Memory in the 8-Arm Radial Maze under Dim Blue and Red Light - Michael Pirchl; Georg Kemmler; Christian Humpel (International Journal of Zoology)
Light intensity and wavelength strongly influence mood and cognition in humans and rodent animal models. The aim of the present study was to explore if dim white (7.6–17.7 lux) , blue (1.3–2.3 lux), and red light (0.8–1.4 lux) affect spatial memory of male and female Sprague Dawley rats in the 8-arm radial maze. Our data show that spatial memory significantly improved within 5 daily learning sessions (each 5 trials) under dim white light, which was not different between male and female rats. However, dim blue and red light significantly reduced spatial learning of female rats in the 8-arm radial maze in the last training session (session 5). In conclusion, we suggest that female Sprague Dawley rats show reduced learning under blue and red light.